CAMP Response Element Binding Protein Expression in the Hippocampus of Rhesus Macaques with Chronic Ephedrine Addiction. (18th October 2017) - Sun, Zongbo; Ma, Ye; Duan, Shouxing; Xie, Lei; Lv, Junyao; Huang, Jinzhuang; Lin, Zhirong; Guo, Ruiwei; Ma, Shuhua
Abstract : Background. Drug addiction is classified as a chronic relapse nature brain disease with complicated neurobiology mechanisms. There are an increasing number of researchers that are investigating the possible mechanisms for solving the thorny problem. Methods . The model of chronic addiction of rhesus monkey ephedrine was established, where changes in body weight and behavior were monitored. The expression of cAMP response element binding protein (CREB) in the hippocampus of rhesus monkeys was identified by real-time PCR and Western blot. Results . We were successful in establishing the chronic ephedrine addiction model in the rhesus macaques. They exhibited changes in body weight and behavior. Immunofluorescence showed that CREB was expressed in the nucleus of the hippocampus, and the expression of CREB mRNA and protein in the hippocampus were increased by real-time PCR and Western blot. The CREB positive expression in the hippocampus of the modeling group was significantly higher than in the control group. Conclusions . The changes of body weight and behavior of the rhesus monkeys after ephedrine chronic addiction were significant. The changes of CREB in the hippocampus of rhesus macaques with ephedrine chronic addiction are important molecular mechanisms, and the upregulation of CREB may be involved in the physiological pathology and behavior process in individuals with chronic ephedrine addiction.